Republic of Estonia : Technical Assistance Report-Public Investment Management Assessment. (IMF Staff Country Reports; Country Report, 2019)
This Technical Assistance Report on the Republic of Estonia highlights that public investment is a priority spending area, and Estonia is seeking to strengthen the efficiency and effectiveness of its capital expenditure from an already high level. Estonia's public investment is relatively efficient, while further improvements should pay attention to the quality of public services enabled by them. Investment implementation is particularly strong. This reflects Estonia's open procurement framework that utilizes an advanced e-procurement system, its modern treasury that employs an effective Treasury Single Account system to guarantee cash availability, asset monitoring that has been made routine through full accrual accounting for the whole public sector, and active project management by ministries. Some practices that are already effectively implemented should be formalized in the institutional design which will act as a safeguard. Public investment projects should be managed in an integrated portfolio at all stages of the investment cycle. It is difficult to obtain a picture of all-important investment projects pursued in the public sector including by local governments and state-owned enterprises. A comprehensive portfolio view of all projects supports transparent prioritization across sectors and the identification of systemic patterns or risks.